Next-Generation Network-Aware SAP Cloud Framework Using LLMs and AI for Financial and Healthcare Analytics (International Journal of Engineering & Extended Technologies Research (IJEETR), 2022)
The increasing reliance on SAP-based cloud platforms for financial and healthcare analytics has amplified the need for intelligent, secure, and network-aware system architectures capable of handling large-scale, sensitive data. Recent advances in Large Language Models (LLMs) and artificial intelligence offer new opportunities to enhance analytical intelligence, automation, and decision support across enterprise environments. This paper proposes a next-generation network-aware SAP cloud framework that integrates LLM-driven analytics with AI-enabled network intelligence to optimize data processing, system performance, and security awareness in financial and healthcare domains. The framework leverages adaptive network monitoring, policy-aware orchestration, and AI-assisted workload management to improve data flow efficiency and analytical accuracy across distributed cloud infrastructures. By incorporating privacy-preserving mechanisms, role-based access control, and intelligent anomaly detection, the proposed architecture supports regulatory compliance while minimizing operational risks. Experimental analysis demonstrates improved scalability, reduced latency, and enhanced resilience against network-level disruptions. The results indicate that combining LLMs and AI with network-aware SAP cloud systems can significantly advance intelligent analytics in mission-critical financial and healthcare applications.
Keywords: Large Language Models; SAP Cloud; Network-Aware Architecture; AI Analytics; Financial Systems; Healthcare Analytics; Cloud Intelligence